STUDY OF THE EFFECT OF ADDING SUNFLOWER OIL AND VITAMIN E TO THE RATIONS ON MILK PRODUCTION, COMPOSITION AND SOME BLOOD PARAMETERS IN AWASSI EWE. - O .D. Al Mallah (Mesopotamia Journal of Agriculture)
This study was conducted by using 24 Awassi ewe , 2-5 years aged, with average body weight 61.75 kg. The ewe were randomly divided into three groups each of eight. Ewe in each group received 1.5 kg/ dry matter of three rations consist mainly of barley, wheat bran, soybean meal and wheat straw . The first group was fed on control ration ( T1 ) ,while 3.5% of sunflower oil were inclusion in the rations of the second ( T2 ) and third (T3 ) groups, with supplement 0.5 g/ ewe / day vitamin E to the feed of ( T3 ). Results showed that the treatments had no significant effect on average body weight, milk production, lactose and protein percentage in milk. Milk Fat percentage was significantly decreased ( P < 0.05 ) in T2 4.55% than T1 5.96%. Also milk energy value lowered significantly ( P < 0.05 ) in T2 3.96 MJ/ kg than T1 4.50 MJ/ kg. Rumen liquor pH before feeding was increased significantly ( P < 0.05 ) in T2 which was 6.8 as compared with T1 6.34, while after 5hr of feeding, pH value of rumen liquor was increased significantly ( P < 0.05 ) in T3 6.2 as compared with T1 and T2 5.8 and 5.65 respectively. Ammonia concentration in rumen liquor and blood parameters was not affected by experimental treatment.